Development of Multimedia Learning Android on Basic Network Engineering Orientation Material Computer and Telecommunication Vocational Schools - Melliana, Wiwik; Diana, Luluk Mauli (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
The era of digitalization of education requires effective learning methods, especially in Informatics subjects. This research develops Android-based learning multimedia for Basic Orientation material for Computer Networks and Telecommunications in Vocational Schools. Multimedia development using the ADDIE model includes Analysis, Design, Development, Implementation, and Evaluation and involves class X TKJ SMKN 1 Sepulu students as research subjects. Data was collected through observation, interviews, and tests. Data analysis was carried out using descriptive and qualitative methods. Two expert validators, material experts and media experts, carried out the validation. The data collection technique uses a questionnaire. Validation results from material experts meet the requirements of 92.5%, which means they are very valid; the media expert results meet the requirements of 92.3%, which means they are valid. At the implementation stage, a trial was carried out. The results of field trials on 30 grade 10 TKJ students obtained an average score of 92.6% with excellent qualifications, which means this medium is accessible for students to learn. The results of testing Android-based multimedia learning show that the media is very suitable as a learning medium for making patterns and helping students' teaching and learning process.